2012
DOI: 10.1002/hbm.22042
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cortico‐striatal‐cerebellar activation during working memory in syndromal and nonsyndromal children with prenatal alcohol exposure

Abstract: Although children with heavy prenatal alcohol exposure may exhibit the distinctive facial dysmorphology seen in full or partial fetal alcohol syndrome (FAS/PFAS), many lack that dysmorphology. This study examined the functional organization of working memory in the brain in three groups of children-those meeting diagnostic criteria for FAS or PFAS, heavily exposed (HE) nonsyndromal children, and healthy controls. A verbal n-back task (1-back and 0-back) was administered to 47 children (17 with FAS/PFAS, 13 HE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 73 publications
2
48
1
Order By: Relevance
“…The activation increases from 0-back to 1-back task were significantly different between controls and PAE subjects in the inferior frontal region (higher in controls), and in the basal ganglia and dorsal prefrontal cortex (higher in PAE subjects) [109].…”
Section: Altered Brain Network Recruitment and Activation In Task Permentioning
confidence: 76%
See 2 more Smart Citations
“…The activation increases from 0-back to 1-back task were significantly different between controls and PAE subjects in the inferior frontal region (higher in controls), and in the basal ganglia and dorsal prefrontal cortex (higher in PAE subjects) [109].…”
Section: Altered Brain Network Recruitment and Activation In Task Permentioning
confidence: 76%
“…Relative to the 0-back task, increased activations in the 1-back task were observed in the left inferior frontal gyrus in controls, and in the dorsal prefrontal cortex, caudate and putamen in nonsyndromal heavily-exposed children, while children with FAS/PFAS showed increased activity in two Crus I/lobule VI and lobule VIIB/VIIIA of the cerebellum and the inferior parietal cortex [109]. The activation increases from 0-back to 1-back task were significantly different between controls and PAE subjects in the inferior frontal region (higher in controls), and in the basal ganglia and dorsal prefrontal cortex (higher in PAE subjects) [109].…”
Section: Altered Brain Network Recruitment and Activation In Task Permentioning
confidence: 86%
See 1 more Smart Citation
“…In fact sex of the non-FASD group only moderated the inhibition standard score results. Sex is rarely explored as a moderator of EF deficits in FASD samples, mainly because sex distributions are similar across FASD and comparison groups (e.g., Aragon et al 2008;Diwadkar et al 2013). Astley et al (2009) directly examined this association and showed that sex does not significantly moderate EF findings (e.g., Astley et al 2009).…”
Section: Factors That Moderate the Fasd-ef Associationmentioning
confidence: 97%
“…143 Image processing and analysis using the SPM12 software package (or earlier versions) has been widely used in previous pediatric samples. 127,[144][145][146] Typical whole brain fMRI analyses using voxel-based methods, like the present study, include more than 50.000 voxels, resulting in numerous statistical tests. Consequently, corrections for multiple comparisons are important in all statistical analyses of fMRI data.…”
Section: Mri Measuresmentioning
confidence: 99%